Acute Type-A aortic dissection with patent false lumen through to the abdominal aorta: effects of a conventional elephant trunk on malperfusion syndromes and narrowed true lumen. (September 2014) - Imura, H; Tanoue, M; Shibata, M; Maruyama, Y; Shirakawa, M; Ochi, M
Background: Narrowed true lumen and patent false lumen through to the terminal aorta is a high-risk condition for malperfusion syndromes (MS) in acute type-A aortic dissection. It is important to ascertain how the true and false lumens behave after surgery. Patients and Methods: We retrospectively investigated 45 patients with this pathology. The true lumen sizes at the narrowest levels above and below the superior mesenteric artery were followed by computed tomography after surgery (0-36 months). Results: Thirty-seven MS were seen in 23 patients. Hospital mortality was 8.9%. The narrowed true lumen was not enlarged in the first 6 months with a patent false lumen. The elephant trunk procedure did not improve the true lumen size. An extremely narrowed (≤3mm) true lumen was associated with a significantly high incidence of MS and mortality. Conclusions: High incidences of MS were observed in this particular pathology. An extremely narrowed true lumen was accompanied by a high incidence of MS and mortality.